Patient safety informatics : adverse drug events, human factors, and IT tools for patient medication safety - Koutkias, Vassilis (IOS Press, 2011)
Improving patient safety and the quality of healthcare poses many challenges, and information technology (IT) can support the measures necessary to address these. Unfortunately, the risk of adverse drug events (ADEs) rises alongside the increasing sophistication of the health IT systems incorporated into hospital environments. These pose a risk to the safety of patients and incur considerable extra healthcare costs. Approaches introduced to eliminate ADEs raise a number of concerns, not least that the successful transferability and use of such tools into real clinical settings is only possible.
Keywords: Medical informatics -- Congresses.; Drugs -- Prescribing -- Safety measures -- Congresses.; Drugs -- Toxicology -- Prevention -- Congresses.; Drugs -- Side effects.; Information storage and retrieval systems -- Hospitals.; Drug-Related Side Effects and Adverse Reactions -- prevention & control; Drug-Related Side Effects and Adverse Reactions; Hospital Information Systems; Safety Management; Medical Informatics; Médecine -- Informatique -- Congrès.; Médicaments -- Prescription -- Sécurité -- Mesures -- Congrès.; Médicaments -- Effets secondaires.; Systèmes d'information -- Hôpitaux.; Médecine -- Informatique.; MEDICAL -- Allied Health Services -- Medical Technology.; MEDICAL -- Biotechnology.; MEDICAL -- Family & General Practice.; MEDICAL -- Lasers in Medicine.; TECHNOLOGY & ENGINEERING -- Biomedical.; Information storage and retrieval systems -- Hospitals; Drugs -- Side effects; Medical informatics; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.